Children of Stressed Parents: a Study Upon Parental Discord, Self-Blame, and Problem Management: Impact of Parental Stress on Children's Mental Health (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Research looking at psychopathology in youth has archivedrates of disorders in children and adolescents approaching those present ingrown-up populations. For instance, information from the Great Smoky Mountains Studyof Youth demonstrate that 39.8% of the children in their sample met criteriafor a psychiatric diagnosis or practical weakness across any of their fouryearly time points (Farmer, Burns, Phillips, Angold, & Costello, 2003).